(untitled) (Global Journal of Human-Social Science, 2019)
The study has to do with the explorations of a way to use the internet services to provide a platform for theuse of individuals groups of people and companies to interact with one another through the social media The social media has really assisted interaction and even bringing together business tycoons and their services together through social networking forums blogs etc